Body of Property: Antebellum American Fiction and the Phenomenology of Possession. - Luck, Chad (Oxford University Press, USA, 2015)
Explores the embodied aspects of ownership and private property as these emerge in a range of American literary texts across the late eighteenth and early nineteenth century.